A political and economic dictionary of Latin America - Calvert, Peter (Europa Publications, 2004)
Latin America, in the first decade of the 21st century, remains as exciting, interesting andunpredictable as ever. In 2004 Haiti, the first Latin American country to gain itsindependence, celebrated its second centenary. But although the structure andorganization of government, politics, production, international relations and trade in theregion are by now well established, important changes are under way, and the LatinAmerican countries are becoming more important than ever before in world politics as abridge between the USA and the rest of the world. This Political and EconomicDictionary of.